2008
DOI: 10.1088/0964-1726/18/1/015005
|View full text |Cite
|
Sign up to set email alerts
|

Cycle energy control of magnetorheological dampers on cables

Abstract: The dissipated cycle energy of magnetorheological (MR) dampers operated at constant current results from controllable hysteretic damping and from almost current independent, small viscous damping. Thus, the emulation of Coulomb friction and linear viscous damping necessitates current modulation during one vibration cycle and therefore current drivers. To avoid this drawback, a cycle energy control (CEC) approach is presented which controls the hysteretic MR damper part such that the total MR damper energy equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…A linear viscous damper with the optimal coefficient is assumed to be attached at location x d / L = 2 %. The harmonic excitation of the first mode of the cable is similar to fw(),xt={center0.6normalsin()πxtrue/Lnormalsin()ω1tt0.2em10normalscenter0t>10normals …”
Section: Numerical Simulation On Control Of Stay Cable Vibration Usinmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear viscous damper with the optimal coefficient is assumed to be attached at location x d / L = 2 %. The harmonic excitation of the first mode of the cable is similar to fw(),xt={center0.6normalsin()πxtrue/Lnormalsin()ω1tt0.2em10normalscenter0t>10normals …”
Section: Numerical Simulation On Control Of Stay Cable Vibration Usinmentioning
confidence: 99%
“…However, the current driver is necessary to control the MR damper in real time. To avoid the using of current driver, amplitude‐independent and frequency‐independent cycle energy control by MR dampers have been studied and applied in some bridges by Weber et al .…”
Section: Introductionmentioning
confidence: 99%
“…This observation is in agreement with the numerical analysis of a taut string with uncontrolled friction damper as shown in and the experimental results shown in . It is therefore concluded that the predominant friction force must be controlled depending on the actual vibration state of the cable as shown in where a controllable friction damper was used. If c mr ≠ 0 , the friction force must also be controlled to avoid the aforementioned drawbacks.…”
Section: Magnetorheological Damper In Passive Modementioning
confidence: 99%
“…Magnetorheological (MR) dampers have been used for controlled structural damping because these semi‐active devices provide the possibility to combine the advantages of passive and active control, and the residual force at 0 A ensures some failsafe performance during a power break down . As shown in, for example, , MR dampers have been successfully used for controlled damping and optimal control of stay cables. Similar numerical and experimental investigations including hybrid testing were conducted in, for example, , for the vibration reduction of buildings equipped with controlled MR dampers.…”
Section: Introductionmentioning
confidence: 99%